Scientific Findings on the Quality of River Buffalo Meat and Prospects for Future Studies - Cruz-Monterrosa, Rosy; Mota-Rojas, Daniel; Ramirez-Bribiesca, Efren; Mora-Medina, Patricia; Guerrero-Legarreta, Isabel (Journal of Buffalo Science, 2020)
The objectives of this review are to detect scientific findings and areas of opportunity in the study of river buffalo meat from primary production through commercialization and to establish future areas of research linked to each step of the meat supply chain to strengthen and improve the production and quality of buffalo meat in the future. Recent studies show that buffalo meat is healthy and that the prevalence of cardiovascular and cerebrovascular diseases is not related to intramuscular fat consumption. The current grand demand for food constitutes an ongoing challenge for agricultural production. Of course, this demand includes meat, but the animal species traditionally destined for human consumption are no longer capable of satisfying requirements. This review detected gaps in studies of the alimentary systems of this species (including its digestive tract) and a paucity of analyses designed to determine the optimum slaughtering age. Identifying –and correcting– practices that foster contamination, reduce the shelf life of buffalo meat, and suggest appropriate conservation and packaging methods during commercialization are two additional pending concerns. This study concludes that marketing buffalo meat represents a great challenge for producers and researchers, one that requires a multi- and interdisciplinary approach that examines in detail every step of the productive chain.